Exercise with blood flow restriction: an effective alternative for the non‐pharmaceutical treatment for muscle wasting. Issue 2 (27th February 2019) - Conceição, Miguel S.; Ugrinowitsch, Carlos
Abstract: Significant muscle wasting is generally experienced by ill and bed rest patients and older people. Muscle wasting leads to significant decrements in muscle strength, cardiorespiratory, and functional capacity, which increase mortality rates. As a consequence, different interventions have been tested to minimize muscle wasting. In this regard, blood flow restriction (BFR) has been used as a novel therapeutic approach to mitigate the burden associated with muscle waste conditions. Evidence has shown that BFR per se can counteract muscle wasting during immobilization or bed rest. Moreover, BFR has also been applied while performing low intensity resistance and endurance exercises and produced increases in muscle strength and mass. Endurance training with BFR has also been proved to increase cardiorespiratory fitness. Thus, frail patients can benefit from exercising with BFR due to the lower cardiovascular and join stress compared with traditional high intensity exercises. Therefore, low intensity resistance and endurance training combined with BFR may be considered as a novel and attractive intervention to counteract muscle wasting and to decrease the burden associated with this condition.